Keabsahan Penyidikan Atas Putusan Praperadilan - Riyanto, Arif; Yanuar Chandra, Tofik; Basuki (Prodi Hukum S1 - Fakultas Hukum - Universitas Pamulang, 2024)
Law enforcement is a system that includes harmony between values ​​and rules and real human behavior. Pretrial is a part of the district court which carries out a supervisory function, especially in cases of coercive efforts against suspects by investigators or public summons. The supervision referred to is supervising how a law enforcement officer exercises the authority vested in him in accordance with the provisions of existing laws and regulations, so that law enforcement officers do not exercise arbitrarily. Legal efforts in the criminal process can be said to be part of the law enforcement process. This can be understood because in essence legal action is also an effort to realize the idea of ​​achieving justice or legal certainty.